Wood composites - Ansell, Martin P. (Woodhead Publishing series in composites science and engineering, 2015)
Recent progress in enhancing and refining the performance and properties of wood composites by chemical and thermal modification and the application of smart multi-functional coatings have made them a particular area of interest for researchers. Wood Composites comprehensively reviews the whole field of wood composites, with particular focus on their materials, applications and engineering and scientific advances, including solutions inspired biomimetrically by the structure of wood and wood composites. Part One covers the materials used for wood composites and examines wood microstructure, and wood processing and adhesives for wood composites. Part Two explores the many applications of wood composites, for example plywood, fibreboard, chipboard, glulam, cross-laminated timber, I-beams and wood-polymer composites. The final part investigates advances in wood composites and looks at the preservation and modification of wood composites, environmental impacts and legislative obligations, nano-coatings and plasma treatment, biomimetic composite materials, the integration of wood composites with other materials and carbonized and mineralized wood composites